Slowdown in Emerging Markets : Sign of a Bumpy Road Ahead? - Tsounta, Evridiki (IMF Working Papers; Working Paper ;, 2014)
Following very strong growth during the period 2000-12, emerging market economies (EMEs) experienced a slowdown in the last couple of years. This paper examines the supply-side drivers of the strong growth performance of 63 EMEs and investigates if the recent slowdown in growth is transitory or a more permanent phenomenon. We find that on average the recent slowdown is explained equally by structural and cyclical factors, although there are large variations across countries and regions. While the cyclical component of the slowdown can be corrected by countercyclical policies (provided that there is sufficient policy space), structural bottlenecks are harder to address. Given the expected moderation of capital accumulation and some natural constraints on labor, the strong growth momentum of 2000-12 is unlikely to be repeated going forward, unless TFP performance improves significantly via structural reforms.